1998
DOI: 10.1016/s0022-5223(98)70399-x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical analysis of small-sized peripheral lung cancer

Abstract: Compared with the patients with lesions 2.1 to 3 cm in diameter, the patients with small-sized lung cancer had a milder progressive state and a better prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
35
0
2

Year Published

2001
2001
2016
2016

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 88 publications
(40 citation statements)
references
References 11 publications
3
35
0
2
Order By: Relevance
“…Previous studies reported better postoperative outcomes and less pathological invasiveness in NSCLC patients with tumors ≤2 cm than in those with larger tumors (2.1-3 cm) (4,16). Favorable postoperative prognosis was evident even in patients with small tumors undergoing limited resection (17).…”
Section: Discussionmentioning
confidence: 78%
“…Previous studies reported better postoperative outcomes and less pathological invasiveness in NSCLC patients with tumors ≤2 cm than in those with larger tumors (2.1-3 cm) (4,16). Favorable postoperative prognosis was evident even in patients with small tumors undergoing limited resection (17).…”
Section: Discussionmentioning
confidence: 78%
“…Regional recurrence may be caused by intrapulmonary metastasis in segments other than the Table 4 for details b Patients in the compromised group did not undergo systemic lymph node dissection specimen segment(s) in the same lobe, by regional lymph node metastasis, or by an incomplete resection margin. The incidence of regional lymph node metastasis and intrapulmonary metastasis in the same lobe has been reported to be 2% and 10%, respectively, in cases of stage I NSCLC [1,9,17,19,20,23]. In our own series of pathologic investigations of 101 stage I NSCLC patients who underwent lobectomy, intrapulmonary metastasis in the resected lobe was found in 2% of patients and mediastinal or lobar lymph node metastasis was found in 10.9%.…”
Section: Discussionmentioning
confidence: 78%
“…A lobectomy is the standard surgical procedure even for small lung cancers, because some studies have demonstrated progressive disease in 10%-20% of patients with small lung cancers. 4,8 Many reports defi ne small lung cancers as having a maximum diameter of 2 cm or less, [1][2][3][4]8 and since adenocarcinoma has been reported to account for 85%-90% of small peripheral lung cancers, 1-3 in this study we restricted our analysis of small peripheral lung cancers to adenocarcinomas. Postoperatively, 89% of the patients (465) had stage IA disease, while the other 11% had progressive disease.…”
Section: Discussionmentioning
confidence: 99%
“…The overall 5-year survival rate of the patients in the present study was 83.6%. Koike et al 4 reported a 5-year survival rate of 79.5% for patients with peripheral cT1N0M0 lung cancer having a maximum diameter of 2 cm or less. Okada et al 12 reported a 5-year survival rate of 87.3% for patients with cT1N0M0 non-small cell carcinoma 2 cm or less in diameter who underwent an extended segmentectomy, and of 77.7% for those who underwent a lobectomy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation